2019
DOI: 10.3390/pharmaceutics11010037
|View full text |Cite
|
Sign up to set email alerts
|

Immediate-Release Nifedipine Binary Dry Powder Mixtures with Nanocellulose Featuring Enhanced Solubility and Dissolution Rate

Abstract: Nifedipine (NIF) is a 1,4-dihydropyridine-based calcium channel blocker with poor solubility, whose bioavailability is highly dependent on the type of formulation. Dry powder mixtures of 20% w/w NIF with microcrystalline cellulose (MCC) and its high surface area nanocellulose analogue, which is namely Cladophora (CLAD) cellulose, were produced by heating at the melting temperature of the drug for 1 h. Non-heated samples were used as a reference. The solid-state properties of the mixtures were characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…IBU, a typical nonsteroidal anti-inflammatory drug, is broadly exploited to treat pain, fever and inflammation. However, its poor water solubility always limits its fast action for achieving a desired therapeutic effect [46,47,48]. HPMC is commonly utilized as an excipient in oral tablet, eye drops, and capsule formations.…”
Section: Introductionmentioning
confidence: 99%
“…IBU, a typical nonsteroidal anti-inflammatory drug, is broadly exploited to treat pain, fever and inflammation. However, its poor water solubility always limits its fast action for achieving a desired therapeutic effect [46,47,48]. HPMC is commonly utilized as an excipient in oral tablet, eye drops, and capsule formations.…”
Section: Introductionmentioning
confidence: 99%
“…The cellulose batches used in this study were identical to those used previously [12,13]. Notably, the pore volume of CLAD was 276 times and the specific surface area of CLAD was about 108 times larger than that for MCC as derived from N 2 gas sorption analysis.…”
Section: Resultsmentioning
confidence: 95%
“…We have previously shown that heat-assisted mixing of poorly soluble drugs from varying pharmacological classes with high surface area nanocellulose results in enhanced solubility and dissolution rate in biorelevant media. In particular, the latter effect was shown for NSAIDs from arylpropionic acid derivatives, e.g., ibuprofen, flurbiprofen, ketoprofen, and naproxen [12], as well as dihydropyridine-type calcium channel blockers, e.g., nifedipine, felodipine [13]. In this article, we extend this strategy and demonstrate improved formulation for a model problem drug featuring both poor solubility and unusually high number of polymorphs.…”
Section: Introductionmentioning
confidence: 83%
“…)-2,6-dimethyl-3,5-dicarbomethoxy-1,4-dihydropyridine (Nifedipine) is a calcium channel blocker drug used for the treatment of angiocardiopathy. Although oral administration is the best convenient route and has better patient compliance, bioavailability of nifedipine has been limited by poor solubility, photo-instability, or short plasma half-life [1]. Nifedipine is a BCS class II agent with a solubility of 5-6 µg/mL in the pH range from 4 to 13 [2], resulting in low bioavailability [3].…”
Section: -(2-mentioning
confidence: 99%